The Role of Women's Agricultural Workers and Household Economic Resilience - Wardihan Sabar; Abd. Rahim; Aulia Rahman Bato (Universitas Pendidikan Ganesha, 2023)
The involvement of women in the agricultural sector can be viewed in various aspects of social, economic, political, cultural, and religious life. This article describes the role of women's agricultural workers concerning household economic resilience, both before and during the COVID-19 pandemic. This research also seeks to systematically reveal the factors that encourage women to choose to become agricultural workers compared to other sectors and the obstacles they face in efforts to increase household economic resilience. This research uses a qualitative approach with the type of case study. This study involved six informants who were selected using a purposive technique. Documentation techniques and in-depth interviews were carried out for data collection. The results showed that women had an essential contribution to the economic resilience of farmer households before and during the COVID-19 pandemic. The pattern of short-term farming ranging from 3-4 months is seen as needing to be more prospective to support the family's economy. Economic background, education background, low skills, and the perception of independent women are seen as factors causing women to work as agricultural workers to help with family finances. The role of women is significant in maintaining household economic resilience both before and during the COVID-19 pandemic. Urgent basic needs can be met even though most are at the minimum level of fulfillment. The expertise of women farm workers in managing and allocating income positively impacts aspects of family economic resilience during the COVID-19 pandemic.